Development of advanced nanotechnology process for sensing materials - Tan, Ooi Kiang. (2008)
Nanotechnology is set to revolutionize the conventional “top-down” manufacturing approach with a new class of materials termed as nanostructured materials. This new class of materials, often characterized by a physical dimension of 1 to 100 nm in at least one dimension and the presence of very high surface area, has found potential application in many areas such as electronics, magnetism, optics, energy storage, electrochemistry and biomedical sciences. The controlled synthesis of nanostructured materials is vital to the success of nanotechnology where various synthesis methods have since been introduced. In this project, we propose a custom-designed inductively coupled plasma chemical vapor deposition (ICP-CVD) system as an alternative manufacturing approach for nanostructured materials. Tin oxide, one of the most studied n-type semiconductors used in the field of gas sensing was chosen as the coating material to establish the promise of the ICP-CVD system. Nanostructured tin oxide plays a prominent role in gas sensing where it has been reported to enhance the sensitivity and the response time of the gas sensors. The ICP-CVD system has been described in terms of the design consideration involved and the implementation work that integrates the various functional modules into a fully working thin film deposition system. Flexibility has been the underlying design concept to make different configurations possible with the ICP-CVD system, hence enhancing its versatility in nanotechnology venture. Alternative precursor delivery route for direct liquid injection and provisions for different precursor entry points into the deposition chamber are among the features offered by the ICP-CVD system.Various deposition configurations have been successfully realized using the novel system during the development phase of the nanotechnology deposition process.